IL-17 induces hyperalgesia via TNF-dependent neutrophil infiltration. - McNamee, K; Alzabin, S; Hughes, J; Anand, P; Feldmann, M; Williams, R; Inglis, J (2011)
Interleukin-17 (IL-17) and tumour necrosis factor-α (TNF) are critical in the pathogenesis of arthritis but their relationship during inflammatory pain has received limited attention. We aimed to establish whether IL-17 can induce hyperalgesia in acute conditions, and investigated the role of TNF in mediating the pain response. Hyperalgesia was elicited in C57BL/6 mice by injection of recombinant IL-17, TNF or vehicle into the plantar tissue. Elevated pain was measured by the Hargreaves test for thermal hyperalgesia and Linton incapacitance tester for weight-bearing change. Cellular infiltration during hyperalgesia was determined by histological analysis and myeloperoxidase assay. IL-17 was found to induce hyperalgesia, but this was dependent on neutrophil migration and TNF binding to TNF receptor 1 (TNFR1). Because TNF-induced hyperalgesia was also dependent on neutrophil migration, the relationship between the resident fibroblasts, the cytokines and the migrating neutrophils was further investigated. By means of an air pouch model of cell migration, it was established that IL-17-induced neutrophil infiltration was dependent of TNF/TNFR1 as this interaction was required for the induction of the chemokine keratinocyte chemoattractant. These findings suggest that IL-17 causes acute hyperalgesia indirectly by inducing TNF from resident cells. The subsequent production of keratinocyte chemoattractant then triggers neutrophil chemotaxis to the plantar tissue, releasing algesic mediators locally to sensitise the nerve.